Recent Progress of Two-Dimensional Thermoelectric Materials - Li, Delong; Gong, Youning; Chen, Yuexing; Lin, Jiamei; Khan, Qasim; Zhang, Yupeng; Li, Yu; Zhang, Han; Xie, Heping (Nano-Micro Letters, 2020)
Thermoelectric generators have attracted a wide research interest owing to their ability to directly convert heat into electrical power. Moreover, the thermoelectric properties of traditional inorganic and organic materials have been significantly improved over the past few decades. Among these compounds, layered two-dimensional (2D) materials, such as graphene, black phosphorus, transition metal dichalcogenides, IVA–VIA compounds, and MXenes, have generated a large research attention as a group of potentially high-performance thermoelectric materials. Due to their unique electronic, mechanical, thermal, and optoelectronic properties, thermoelectric devices based on such materials can be applied in a variety of applications. Herein, a comprehensive review on the development of 2D materials for thermoelectric applications, as well as theoretical simulations and experimental preparation, is presented. In addition, nanodevice and new applications of 2D thermoelectric materials are also introduced. At last, current challenges are discussed and several prospects in this field are proposed. Highlights: 1 A comprehensive review on the recent development of two-dimensional (2D) nanomaterials for bulk or thin-film thermoelectric materials, as well as composite filler, has been extensively presented. 2 Development of micro-device platform and its application to study the inherent thermoelectric properties of individual single- and few-layer 2D nanomaterials.